PENGARUH KINERJA KEUANGAN DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY (CSR) SEBAGAI VARIABEL PEMODERASI (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2019) - Dewi Kusuma Wardani; Nova Dwi Lestari (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2022)
This study aims to examine the effect of financial performance and capital structure on firm value with Corporate Social Responsibility (CSR) as a moderating variable. The sample used in this study is a manufacturing company listed on the Indonesia Stock Exchange Bursa Efek Indonesia (BEI). 2016-2019. Sampling using purposive sampling method and obtained 64 companies. This study uses multiple regression analysis and Moderated Regression Analysis (MRA). The results showed that financial performance had an effect on firm value. Capital structure has no effect on firm value. Corporate Social Responsibility (CSR) is unable to moderate the effect of financial performance on firm value. Corporate Social Responsibility (CSR) is unable to moderate the effect of capital structure on firm value.